Local Wisdom and Identity Represented by Pudak - Elisabeth Christine Yuwono; Listia Natadjaja (Universitas Brawijaya, 2018)
As an archipelago, Indonesia is rich in cultures that exist and grow in its unique regions. It could be influenced by people's habits, thoughts, acts, and geographical characteristics, creating certain values, rec-ognized as local wisdom. Gresik, a small city at the edge of East Java northern coast, has distinctive features; one of them is its traditional snack: Pudak. Traditional snacks are typical because they can be found only in specific regions. As a traditional snack, Pudak has a unique package made of natural material, that is ope. As a cultural product, Pudak and its packaging have interesting local values. This research shows that the making process, packaging materials, and packaging process of Pudak which are the local wisdom and the identity of Gresik. This identity is important because in this globalization era, many people do not know or even care about the cultural meaning of traditional snacks.